(untitled) (American Journal of Business Management, Economics and Banking, 2025)
The article provides an in-depth examination of the application of digital technologies in analyzing the activities of commercial banks in Uzbekistan, their impact on efficiency, and their role in improving service quality. In recent years, digital transformation processes in the national banking system have accelerated sharply, leading to a significant increase in the share of remote services. According to data from the Central Bank, between 2018 and 2023 the number of electronic transactions increased 12-fold and their value grew 9-fold, clearly demonstrating the rapid development of digital services. The study analyzes statistics from 2020–2024, current regulatory and legal documents, as well as innovative solutions used in commercial banks such as HumoPay, QR-Online, remote identification, and artificial intelligence modules. Empirical analyses confirm that increasing the level of digitalization in banking operations has a direct positive effect on service speed, the reduction of operational costs, and the growth in the number of customers.